2020
DOI: 10.1007/s00330-020-07353-z
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal photoacoustic/ultrasonic imaging system: a promising imaging method for the evaluation of disease activity in rheumatoid arthritis

Abstract: Objectives We aimed to assess the clinical value of multimodal photoacoustic/ultrasound (PA/US) articular imaging scores, a novel imaging method which can reflect the micro-vessels and oxygenation level of inflamed joints of rheumatoid arthritis (RA). Methods Seven small joints were examined by the PA/US imaging system. A 0–3 scoring system was used to semi-quantify the PA and power-Doppler (PD) signals, and the sums of PA and PD scores (PA-sum and PD-sum scores) of the seven joints were calculated. The rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…[1][2][3][4][5] Since a growing body of evidence indicates the importance of bioimaging technology, numerous kinds of bioimaging technologies, such as computed tomography (CT), single photon emission CT (SPECT), positron emission tomography (PET), X-ray imaging, radiation imaging, Raman imaging, magnetic resonance imaging (MRI), fluorescence imaging, ultrasonic imaging and photoacoustic imaging, have been developed for the diagnosis and determination of diseases in the laboratory, and preclinical and clinical trials. [4][5][6][7][8][9][10][11][12] Among them, owing to its outstanding advantages of rapid and sensitive feedback, multiple signal acquisition capability, high temporal resolution, as well as maneuverable instruments, the non-invasive fluorescence imaging method has been employed as a powerful tool for labeling and tracing specific molecules, proteins and organelles in living cells and even whole animals, and is hence capable of imaging and monitoring different diseases, [13][14][15][16][17][18][19] such as ocular diseases, different bacterial infections, cancer and lymph node (LN) metastasis. Fluorescence imaging can also be utilized to guide surgery in the treatment of disease.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Since a growing body of evidence indicates the importance of bioimaging technology, numerous kinds of bioimaging technologies, such as computed tomography (CT), single photon emission CT (SPECT), positron emission tomography (PET), X-ray imaging, radiation imaging, Raman imaging, magnetic resonance imaging (MRI), fluorescence imaging, ultrasonic imaging and photoacoustic imaging, have been developed for the diagnosis and determination of diseases in the laboratory, and preclinical and clinical trials. [4][5][6][7][8][9][10][11][12] Among them, owing to its outstanding advantages of rapid and sensitive feedback, multiple signal acquisition capability, high temporal resolution, as well as maneuverable instruments, the non-invasive fluorescence imaging method has been employed as a powerful tool for labeling and tracing specific molecules, proteins and organelles in living cells and even whole animals, and is hence capable of imaging and monitoring different diseases, [13][14][15][16][17][18][19] such as ocular diseases, different bacterial infections, cancer and lymph node (LN) metastasis. Fluorescence imaging can also be utilized to guide surgery in the treatment of disease.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have addressed the use of exogenous PA contrast agents combined with drugs as the imaging or therapeutic medium for RA [29] , [46] , [47] . Currently, PAI is not only limited to animal models, and relevant imaging devices and techniques are already available in the clinic [48] , [49] , [50] . One study examined seven small joints in humans using a PA/US imaging system to measure relative oxygen saturation values in inflamed joints and showed that the sub-PA score was highly positively correlated with the standard clinical score for RA.…”
Section: Introductionmentioning
confidence: 99%
“…In the PA imaging system, there are several common types of ultrasound transducers [10], such as single-element transducers [11], handheld linear transducers [12], and curve-array or ring-array transducers [7,[13][14][15]. Photoacoustic computed tomography (PACT), as a common form of PA imaging, has shown the excellent potential in clinical applications, including monitoring the circulating tumor cells [16], whole-body imaging for small animals [14], imaging for cancer and inflammation [13,14], therapy monitoring and molecular imaging [17].…”
Section: Introductionmentioning
confidence: 99%